The Investigation of Mixed Ferrofluids Containing Iron Oxide nanoparticles and Microspheres - Sharanabasava V. Ganachari; Veerabhadragouda B. Patil; Nagaraj R. Banapurmath; Manzoore Elahi M. Soudagar; Kiran Shahapurkar; Ashraf Elfasakhany; Mishal Alsehli; Akshata Yavagal; Pradyumna Mogre; Vijayakumar M Hiremath; Shankar A. Hallad (Advances in Materials Science and Engineering)
The aim of the present work is the synthesis and characterization of iron oxide (Fe3O4) nanoparticles. These nanoparticles are coated with oleic acid and polyvinyl butyral and mixed with microspheres and further developed ferrofluids with silicon oil. Studies of the performance of the nanoparticles in these ferrofluids with and without coating agents were carried out. The nanoparticles were synthesized using the chemical co-precipitation technique and coated with oleic acid and polyvinyl butyral, and it further mixed with microsphere ferrofluids and developed using silicon oil. The prepared Fe3O4 nanoparticles and their coated forms of oleic acid and polyvinyl butyral were mixed with microspheres; furthermore, ferrofluids were developed with silicon oil. All forms of these ferrofluids are characterized for morphology and phase purity (SEM, XRD, and FTIR). The iron oxide (Fe3O4) nanoparticles have shown different magnetic properties, differentiating macroscopic iron oxide in suspended particles. The ratio of surface to volume increases along with the decrease in atomic size, essential for assessing the surface morphological properties. The magneto-rheological (MR) fluids were determined, and shear stress of Expancel microsphere mixed iron oxide nanoparticle with and without them was found almost equal. However, the ferrofluid with PVB coated nanoparticles and microspheres emerged as a stable rheological ferrofluid, sustaining high shear stress and low viscosity with increasing shear rate. Also, shear rates up to 650 s−1 have been observed, showing very high shear stress withstanding capacity. The stability and performance of the magnetic colloidal ferrofluids depend on the thermal contribution and the balance between attractive/repulsive interactions.